The influence of self-efficacy on social adaptability among college students: The mediating role of psychological resilience - Su, Xiaobin; Weng, Fwuyuan (Edelweiss Applied Science and Technology, 2024)
Against the backdrop of rapid social development, given the importance of good social adaptability for individuals’ careers and daily lives, the purposed of this study is to explore the influence of self-efficacy of vocational college students on social adaptability. A questionnaire survey was conducted on 940 vocational college students in China using the Self-Efficacy Scale, Social Adaptability Scale, and Psychological Resilience Scale to obtain valid samples. SPSS and AMOS are used to further explore the explanatory and predictive relationships between variables. A mediation effect is proposed to establish a structural model, and the bias-corrected percentile Bootstrap method is used to conduct an empirical test on the constructed model. The research results show that the self-efficacy of vocational college students in China has a significant positive impact on social adaptability. Moreover, psychological resilience plays a mediating role in the influence of self-efficacy on social adaptability. Based on these results, schools can promote the improvement of students’ social adaptability by cultivating their self-efficacy. Through targeted mental health education and training, students’ self-efficacy and psychological resilience can be enhanced, thereby improving social adaptability and enabling them to better cope with academic pressure and life challenges and adapt to vocational and social lives.